2001
DOI: 10.1038/sj.gt.3301362
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic gene therapy utilizing subcutaneous inoculation of EC-SOD gene transduced autologous fibroblast suppressed lung metastasis of Meth-A cells and 3LL cells in mice

Abstract: We have previously reported that superoxide stimulates the motility of tumor cells and the administration of Cu-Zn superoxide dismutase (SOD) significantly suppresses metastasis. However, ideally, anti-metastatic therapy should be longlasting, systemically effective and have low toxicity. The halflife of Cu-Zn SOD in plasma is so short that it cannot provide long-lasting effects. Therefore, in this study we have developed a gene therapy in a mouse model utilizing extracellular SOD (EC-SOD), which is the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Diphenyleneiodonium has been used to inhibit ROS production mediated by NADPH oxidase in various cell types [21,31,32]. Our immunohistochemical results showed that NADPH oxidase is over-expressed in EOC tissues as compared to normal ovarian tissues (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Diphenyleneiodonium has been used to inhibit ROS production mediated by NADPH oxidase in various cell types [21,31,32]. Our immunohistochemical results showed that NADPH oxidase is over-expressed in EOC tissues as compared to normal ovarian tissues (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…In this study we sought to determine the effects of inhibiting the generation of ROS by DPI, a well-characterized, potent inhibitor of flavoenzymes including NADPH oxidase, on apoptosis of EOC cells, and whether these effects are associated with SOD3 and HIF-1α expression [30,31]. Diphenyleneiodonium has been used to inhibit ROS production mediated by NADPH oxidase in various cell types [21,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial was performed with a topical gel containing liposomally encapsulated recombinant human SOD protein for the treatment of painful Peyronie's disease resulting in a significant pain reduction and high patient satisfaction [47]. Optic neuropathy [48], and neurodegeneration/neurotoxicity [49], ototoxicity [50], arthritis [51,52], cerebral vasospasm [53], tumor growth [54][55][56], liver cholestasis [57], liver damage [58,59], inflammation [60] and erectile dysfunction [61] are some of the experimental diseases where SOD isoforms have shown a notorious recovery of the particular ailment. A most recent approach in gene transfer protocols have focused on a combination of genes or therapies rather than a monogene treatment which have shown improved results for a number of the previously described pathologies [36,46,51,54,56].…”
Section: Other Pathologiesmentioning
confidence: 99%
“…All the techniques have been reported to reverse malignant phenotypes of tumour cells. They are (i) intravenous or subcutaneous administration of recombinant human SOD which substitutes specific amino acid for stable one (Yoshizaki et al, 1994); (ii) intravenous administration of SOD conjugated with a pyran copolymer, for prolongation of its activity (Oda et al, 1989); (iii) addition of exogenous liposomal SOD (Beckman et al, 1988); (iv) intraperiponeal or subcutaneous administration of a selective SOD mimetic molecule of nonpeptidic and low molecular weight (Samlowski et al, 2003); (v) elevation of SOD level by sense cDNA transfection (Safford et al, 1994); (vi) inoculation of fibroblasts that are genetically modified to secrete SOD (Tanaka et al, 2001); (vii) elevation of SOD levels by exposure to a superoxide generator and subsequent isolation of superoxide-resistant cells (FernandezPol et al, 1982); (viii) secondary induction of SOD in tumour ) every day from 2 days before coimplantation to the end of the experiment. All the mice were killed under ether anaesthesia at 28 days after implantation, and serum and tumour tissues were collected for examination.…”
Section: Discussionmentioning
confidence: 99%